9514 1404 393
Answer:
(x1, x2) = (3, -4)
Explanation:
As with any 2-step linear equation, subtract the constant, then multiply by the inverse of the coefficient of the variable.
![\left[\begin{array}{cc}3&2\\5&5\end{array}\right]\left[\begin{array}{c}x\\y\end{array}\right]+\left[\begin{array}{c}1\\2\end{array}\right]=\left[\begin{array}{c}2\\-3\end{array}\right]\\\\\left[\begin{array}{cc}3&2\\5&5\end{array}\right]\left[\begin{array}{c}x\\y\end{array}\right]=\left[\begin{array}{c}1\\-5\end{array}\right]\\\\\left[\begin{array}{c}x\\y\end{array}\right]=(1)/(5)\left[\begin{array}{cc}5&-2\\-5&3\end{array}\right]\left[\begin{array}{c}1\\-5\end{array}\right]](https://img.qammunity.org/2022/formulas/mathematics/college/an4dd4m4cm2vn87ymwn1k66unnmg3183tv.png)
Performing the multiplication of the matrix by the vector gives the solution.
x = ((5)(1) +(-2)(-5))/5 = 15/5 = 3
y = ((-5)(1) +(3)(-5))/5 = -20/5 = -4
Using your variables, x1, x2, the solution is ...
(x1, x2) = (3, -4)